Injectable hydrogels for cartilage tissue engineering: key design needs toward clinical applications - Alma Tamunonengiofori Banigo; Alex Nwekwo; Bram Zoetebier; Marcel Karperien (Academia Biology)
This article reviews injectable hydrogels and their unique properties such as the ability to fill irregular defect sites and support cellular activities. Injectable hydrogels have become invaluable tools for creating three-dimensional (3D) cell-laden scaffolds in cartilage tissue engineering (CTE). This review centers on the design requirements and clinical applications of injectable hydrogels in this domain. We begin by examining material selection, emphasizing the importance of biocompatibility and mechanical properties crucial for successful CTE. Various cross-linking mechanisms are explored, highlighting enzymatic and chemical methods that ensure the stability and functionality of the hydrogels. The review then delves into specific applications of injectable hydrogels in CTE, demonstrating their ability to support chondrocyte function and facilitate extracellular matrix formation. Current clinical trials and commercially available products are underscored, showcasing the progress and potential of these hydrogels in clinical settings. Notable examples include hydrogels utilized for articular cartilage repair and those combined with growth factors to enhance tissue regeneration. Future perspectives for injectable hydrogels in CTE highlight the need for improved mechanical strength, longevity, and better integration with host tissues. Advancements in hydrogel formulations, including the incorporation of bioactive molecules and stimuli-responsive systems, are crucial for further progress in the field. In conclusion, injectable hydrogels represent a versatile and promising approach for CTE. By addressing specific design needs and leveraging advanced production techniques, these hydrogels have the potential to significantly impact clinical applications, offering effective solutions for tissue repair and regeneration.